Antioxidant Activity of Glycerol Derivatives of Fatty Acids from the Fruits of Lycium chinense Miller - Lee, Joohyun; Chung, Ill-Min; Nagella, Praveen; Ahmad, Ateeque (Asian Journal of Chemistry, 2013)
Lycium chinense, a famous Chinese medicinal herb, has long history of use as a traditional remedy for many diseases. Two compounds 1-oleo-2,3-dilinoleioglyceride (1) and 1,2-dioleo- 3-linolenioglyceride (2) were isolated from the ethyl acetate extract of fruits of L. chinense, the antioxidant activity of glycerol derivatives of fatty acids were evaluated by three established methods namely, 1,1-diphenyl-2-picrylhydrazyl (DPPH–) radical scavenging, reducing power and the phosphomolybdenum activities. The antioxidant activity of glycerol derivatives of fatty acids (1 and 2) was evident as it showed significant natural antioxidants.